The Influence of Technopreneurship-Based Strategic Management on Project Performance at PT Len Industri (Persero) - Adhika Ramadhan; Irfan Dwiguna; Eddy Soeryanto; Rahma Wahdiniwaty; Adam Mukaril (Manunggal Halim Jaya, 2026)
This study analyzes the role of technopreneurship-based strategic management in improving the performance of Smart Technology Internet of Things (IoT) E-Bike projects at PT Len Industri (Persero). A quantitative explanatory approach with data triangulation was employed by integrating perception-based assessments with objective project performance indicators derived from Earned Value Management, namely the Schedule Performance Index (SPI) and the Cost Performance Index (CPI). Data were collected through questionnaires administered to project personnel and from official project reports. The results indicate that technopreneurship-based strategic management is implemented at a high level and has a positive and significant effect on project performance. All dimensions, namely productive, creative, innovative, and dynamic, contribute significantly to improving schedule adherence, cost efficiency, system quality, stakeholder satisfaction, and technological reliability. The consistency between subjective assessments and objective performance indicators confirms that project performance can be empirically verified and is not solely based on perceptions. This study concludes that integrating technopreneurship-oriented management with objective performance measurement enhances the effectiveness, efficiency, and accountability of IoT-based technology project management.